Evaluation of the Virtual Economic Effect of Tourism Product Emotional Marketing Based on Virtual Reality - Talafubieke, Manati; Mai, Sheng; Xialifuhan, Nuermila (Frontiers in Psychology, 2021)
Rapid development of Internet technology has led to great changes in all fields of life. Tourism industry has also gone to the Internet with the change of the times. As the application of Internet technology in tourism, virtual reality tourism products are directly used in promoting economic development. Internet tourism stores all kinds of tourism information in database, realizes network roaming, provides convenient information services for both the supply and demand of tourism, and can realize the rapid and stable sustainable development of tourism. This paper mainly studies the evaluation of the virtual economic effect of emotional marketing of tourism products based on virtual reality, the meaning algorithm of virtual reality, etc., analyzes the virtual economy of tourism products based on virtual reality, and helps tourism enterprises to grasp the needs of tourism consumers more accurately, so as to design products and services that are more in line with the demands of tourism consumers, The process of ultimately improving the user value. This paper mainly uses virtual reality method, virtual reality platform eye map processing, virtual reality eye map regional detection and feature extraction method, and virtual reality tourism product emotion marketing related experiments, etc. to study the evaluation of the virtual economic effect of tourism product emotion marketing based on virtual reality. The economic performance information of virtual tourism industry is equivalent to the amount of these indicators, the impact of the comprehensive evaluation on the economic performance of virtual tourism is quite equal. The results show that from 2017 to 2020, the virtual economic revenue of virtual reality tourism product emotional marketing increased from 50million to 1billion. However, people attach more and more importance to the tourism experience brought by virtual tourism products, and the reasonable consumption structure of Virtual Tourism hinders the improvement of tourism economic benefits. In order to promote the rationalization of the consumption structure of virtual tourism, to develop the basic industry of tourism consumption, to increase the non necessities of shopping and processing, to increase the supply of tourism products, and to enrich and enrich tourism consumption.